(untitled) (Biodiversitas Journal of Biological Diversity, 2007)
Î²-Glucan is one of the most abundant polysaccharides in yeast Saccharomyces cerevisiae cell wall. The aim of this research is to explore an alternative nitrogen sources for Î²-glucan production. S. cerevisiae were grown in fermentation medium with different nitrogen sources. Peptone 2%, glutamic acid 0,5%, urea 0,2%, and diammonium hydrogen phosphate (DAHP) 0,02% were used for nitrogen source in the medium. A two liter air-lift fermentor was used in the fermentation process for 84 hours (T = 300C, pH 7, and 1.5 vvm for the aeration). During the fermentation, optical density, extraction of Î²-glucan, glucose and protein in hydrolisate cultured were determined. Î²-glucan production level is similar with the growth rate of yeast and followed by decreasing glucose and protein content in hydrolysis cultured. The highest and lowest Î²-glucan content were obtained from peptone (933.33 mg/L) and glutamic acid (633.33 mg/L) as a nitrogen source in cells cultured after fermentation completed respectively. Yeast cells cultured with urea and DAHP as a nitrogen source give the same content of Î²-glucan about 733.33 mg/L. Î²-glucan concentration produced in medium with urea was a higher than that produced using glutamic acid and DAHP as a nitrogen source. The result indicated that urea can be used as an alternative nitrogen source for the production of Î²-glucan. Urea is easily available and cheaper than peptone, glutamic acid and DAHP. Â© 2007 Jurusan Biologi FMIPA UNS Surakarta Key words: Î²-glucan, Saccharomyces cerevisiae, air-lift fermentor